Iron-Catalyzed Stereoselective Allylboration of 3,4-Dihydroisoquinolines with Potassium Allyltrifluoroborates - Fang, Yong; Hu, Xiaoling; Shi, Zhuangzhuang; Zhao, Xu; Gopireddy, Raveendra Reddy; Luo, Yunfei (Synthesis, 2021)
An iron-catalyzed allyation of isoquinoline with potassium allyltrifluoroborate is described. The operation of this reaction is very simple and highly practical. The diastereoisomer having two adjacent chiral centers were obtained in single anti-configuration.
Keywords: iron catalysis; potassium allyltrifluoroborate; allylboration; tetrahydroquinoline